Newly-developed colonoscope (PCF-PQ260L) is useful for patients with difficult colons - Inoki, Kazuya; Yamada, Masayoshi; Kuwabara, Hiroki; Takamaru, Hiroyuki; Sekiguchi, Masau; Sakamoto, Taku; Matsuda, Takahisa; Saito, Yutaka (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: Preforming total colonoscopy (TCS) is sometimes difficult due to adhesions or long colons. The PCF-PQ260L (PQL) was developed to overcome TCS-related difficulties. The aim of this study was to investigate the performance and usefulness of PQL for difficult colon cases. Materials and Methods: This was a retrospective single center observational cohort study investigating differences in patient characteristics and examination performance between patients examined with PQL, versus standard (SD), scopes. Secondly, we directly compared PQL and SD scopes in patients treated with both types of scope. Results: The PQL was used with 105 patients and SD scopes were used with 1119 patients. Patients in the PQL group were significantly shorter (157cm vs 163cm, p< 0.01) and lighter, compared to the SD group (52 kg vs 58 kg, p< 0.01). There were no significant statistical differences with regard to cecal intubation rate, cecal intubation time, and adenoma detection. Direct comparison of use of PQL and SD scopes on the same patients revealed shorter average cecal intubation time (7 min vs 10 min, p< 0.01), and significantly increased numbers of patients reporting no pain (66 % vs 20 %, p< 0.01) and needing no sedative drugs (48% vs 25 %, p< 0.01) associated with PQL use. Conclusion: The examination performance of the PQL scope was similar to the SD scope. The PQL may be a good option for patients who with difficult colons. Cite this article as: Inoki K, Yamada M, Kuwabara H, et al. Newly-developed colonoscope (PCF-PQ260L) is useful for patients with difficult colons. Turk J Gastroenterol 2019; 30(7): 630-5.